Framing the Conflict: A Comparative Analysis of Tempo.co And Kompas .com's Construction of the Susi Air Pilot Hostage Crisis in Papua - Asnan, Muhammad; Rizki Ashiri, Muhammad Aga; Purnomo, Agung (International Journal of Multidisciplinary Applied and Science Research, 2025)
This research conducts a comparative framing analysis of how two leading Indonesian online media outlets, Tempo.co and Kompas.com, constructed the narrative of the Susi Air pilot hostage crisis involving the Armed Criminal Group (KKB) in Papua. Utilizing Zhongdang Pan and Gerald M. Kosicki's comprehensive framing model, this study examines 22 news articles published between February and July 2023 across four analytical structures: syntactical, script, thematic, and rhetorical. The findings reveal distinct editorial positioning: Tempo.co consistently employs a conflict-centric frame, emphasizing dramatic actions, explicit KKB demands, and critical discourse with negatively connotated lexicon. In contrast, Kompas.com adopts a state-procedural frame, focusing on institutional handling, security protocols, and official statements while maintaining formal neutrality. This divergence demonstrates how competing media ideologies produce alternative realities of the same event, with Tempo.copositioning as a "watchdog" critical of state authority and Kompas.com aligning with state narratives to project stability. The research contributes to media studies by applying established framing theory to the underexplored context of Papuan conflict reporting and provides insights into journalistic ethics in covering sensitive national security issues.